The Sustainability Status of Ujong Baroh Fish Landing Port Facility Management in West Aceh District, Indonesia - Cut Putriyani Meutia; Sugianto Sugianto; Edwarsyah Edwarsyah (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Ujong Baroh Fish Landing Port (FLP) is a type D fishing port which is an important infrastructure in small-scale capture fisheries activities. But there are some obstacles in the management of the FLP. Improper management can have an impact on the optimal utilization of facilities and activities that are not active. This is a challenge for the Regional Government of West Aceh. Therefore, Meulaboh FLP needs to be supported by a suitable management by involving the relevant agencies. Thus this research is very important to be carried out regarding the sustainability status of the optimal management of Fish Landing Port facilities. The results of the study showed that there are four dimensions that have sustainability covering the ecological dimension 57.43, economic dimensions 62.93, socio-cultural dimensions 76.08, technological dimensions 57.54, with 24 attributes while there is one institutional dimension 32.76 by having 6 attributes that do not have less sustainability in managing Ujong Baroh Fish Landing Port facilities